The Effects of Computers on Children's Social Development and School Participation: Evidence from a Randomized Control Experiment - Robert W. Fairlie; Ariel Kalil (Institute for the Study of Labor (IZA), 2016)
Concerns over the perceived negative impacts of computers on social development among children are prevalent but largely uninformed by plausibly causal evidence. We provide the first test of this hypothesis using a large-scale randomized control experiment in which more than one thousand children attending grades 6-10 across 15 different schools and 5 school districts in California were randomly given computers to use at home. Children in the treatment group are more likely to report having a social networking site, but also report spending more time communicating with their friends and interacting with their friends in person. There is no evidence that computer ownership displaces participation in after-school activities such as sports teams or clubs or reduces school participation and engagement.
Keywords: I20; 330; computers; ICT; education; social development; school participation; experiment